2012
DOI: 10.1124/dmd.112.045476
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Human Intestinal Glucuronidation Effects on Intestinal Availability of UDP-Glucuronosyltransferase Substrates Using In Vitro Data

Abstract: ABSTRACT:We investigated whether the effects of intestinal glucuronidation on the first-pass effect can be predicted from in vitro data for UDP-glucuronosyltransferase (UGT) substrates. Human in vitro intrinsic glucuronidation clearance (CL int, UGT ) for 11 UGT substrates was evaluated using pooled intestinal microsomes (4.00-4620 l ⅐ min ؊1 ⅐ mg ؊1) and corrected by the free fraction in the microsomal mixture (CLu int , UGT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…27) Therefore, a pan-UGT inhibitors would also be beneficial for drug discovery. Nakamori et al have reported that quercetin was metabolized by 12 different subtypes of UGT-overexpressed supersomes including the UGT1A and 1B family, 28) postulating quercetin as a potential pan-inhibitor to UGT metabolism. The present study revealed that quercetin can reduce both MPAG and AcMPAG accumulation in SCH with a concomitant increase in MPA accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…27) Therefore, a pan-UGT inhibitors would also be beneficial for drug discovery. Nakamori et al have reported that quercetin was metabolized by 12 different subtypes of UGT-overexpressed supersomes including the UGT1A and 1B family, 28) postulating quercetin as a potential pan-inhibitor to UGT metabolism. The present study revealed that quercetin can reduce both MPAG and AcMPAG accumulation in SCH with a concomitant increase in MPA accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The K i value of telmisartan for CPT-11 hydrolysis by HLM (1.2 6 0.1 mM) was 10-fold higher than the estimated concentration of telmisartan in the liver. In contrast, the concentration of telmisartan in the intestine in which CES2 is highly expressed was predicted to be 31 mM (Nakamori et al, 2012). Thus, telmisartan may exhibit a DDI with compounds that are substrates of CES2 via inhibition of CES2 in the intestine but not in the liver.…”
Section: Downloaded Frommentioning
confidence: 97%
“…2 ) can be relatively straightforward and ‘minimal’ models, such as Q Gut , require only in vitro metabolic CL int and cell permeability data to estimate F G . Several groups have reported successful prediction of F G in animals [ 242 , 243 ] and humans [ 49 , 227 , 228 , 244 , 245 ] with this approach. Drugs with high in vivo extractions ( F G values <0.5) were less accurately predicted and may reflect inability of the Q Gut model to account for changes in enterocyte drug concentration and therefore saturation of DME and efflux transporter processes [ 246 ].…”
Section: Preclinical Models For the Prediction Of F mentioning
confidence: 99%